DENSITY DISTRIBUTION PROBABILITIES ANGLE ORIENTATION OF POLARIZATION PLATE IN TRACKING - A. I. Loqvin; E. A. Lutin; A. N. Zajtsev (Научный вестник МГТУ ГА, 2016)
Density distribution probabilities angle orientation of polarization plate in tracking radar are considered.